A comparative study on outcome of ileal perforation after primary perforation closure and resection and ileostomy - A., Khalilur Rahman; Krishnaswamy, Jawahar; G., Muthukumaran; J., Sanjay Prakash (International Surgery Journal, 2018)
Background: Ileal perforations are a common occurrence in our hospital setup with a majority of cases having an etiology of typhoid. The presentation and management of ileal perforation with special reference to typhoid, nonspecific and traumatic perforations and the outcomes in these patients and the factors affecting prognosis are important. Aims and objectives of the study were to study the management of Ileal perforation. To compare the outcome of two different types of treatment for Ileal perforation i.e. Primary Closure (vs) Resection and Ileostomy. Methods: This is a randomized comparative observational study conducted in general surgery department of Saveetha Medical College and Hospital, Chennai between February 2016 to October 2017. A Minimum of 28 patients was included in the study. Diagnosis was made on the basis of the X-ray erect abdomen, ultrasound abdomen, Widal test and intra-operative findings. Results: The common age groups affected was 41-50 years age group (5 patients) and 61-70 years age groups (5 patients). The least affected were 1-10years age group (one patient). The incidence in males was slightly greater than females. Male to female ratio was 2.5:1. Typhoid perforation is the most common case of ileal perforation followed by non-specific perforation. Post-operative complications are more in the primary closure group with 32.14% (9 patients) which is lower when compared to ileostomy group 17.85% (5 patients). Complications of primary closure were wound infection (2 patients), burst abdomen (3 patients), faecal fistula (1 patient), respiratory complications (3 patients). Complications in ileostomy group were wound infection (4 patients) and respiratory complications (one patient). Conclusions: Mortality was more in primary closure group with 21.42% (6 patients) and mortality was less in ileostomy group with 7.14% (2 patients). This study proposes that ileostomy may be given priority over other surgical options in moribund patients.